Genomics of lung cancer - Govindan, Ramaswamy (Henry Stewart Talks, 2016)
Complexity of the lung cancer genome, Molecular classification of subtypes, Pathways of activation in tumors, Intratumoral heterogeneity, Targetable alterations in patients, Emerging areas in genomics of lung cancer